2021
DOI: 10.3390/brainsci11060710
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Chorea—HIV Infection Delays Diagnosis of Huntington’s Disease by Years

Abstract: Background: There is a broad range of potential differential diagnoses for chorea. Besides rare, inherited neurodegenerative diseases such as Huntington’s disease (HD) chorea can accompany basal ganglia disorders due to vasculitis or infections, e.g., with the human immunodeficiency virus (HIV). The clinical picture is complicated by the rare occurrence of HIV infection and HD. Methods: First, we present a case suffering simultaneously from HIV and HD (HIV/HD) focusing on clinical manifestation and disease ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…All sites are required to obtain and maintain local ethical approval. We investigated the periodic dataset five (PDS5), as described previously [ 33 , 34 ] Ethics approval was obtained by the local ethics committee of Ruhr-University Bochum (No. 4941-14).…”
Section: Methodsmentioning
confidence: 99%
“…All sites are required to obtain and maintain local ethical approval. We investigated the periodic dataset five (PDS5), as described previously [ 33 , 34 ] Ethics approval was obtained by the local ethics committee of Ruhr-University Bochum (No. 4941-14).…”
Section: Methodsmentioning
confidence: 99%
“…The authors recommend a careful family history and strong consideration of HD testing to be included in any case of suspected HIV-associated chorea. 53 Despite its reputation as the great mimicker, neurosyphilis appears to be a rare cause of chorea, at least in the modern era, and is usually concomitant with HIV infection. One case report of a 70-year-old HIV-negative man who presented with 10 years of chorea and a positive CSF Venereal Disease Research Laboratory (VDRL) and Fluorescent treponemal antibody absorption (FTA-ABS) test was reported in 2009.…”
Section: Infectious/para-infectiousmentioning
confidence: 99%
“…55 Due to this nonspecific presentation, there is clinical overlap between HIV-associated chorea and early HD, which can delay diagnosis of the latter. 53 It is also suggested that the concomitant HAD and HD will result in earlier onset of symptoms and a more severe phenotype. One study using data from the ENROLL-HD database found that of 10,000 HD manifest patients, the 25 patients who were also HIV positive had a longer lag time, on average about 2 years, between onset of symptoms and HD diagnosis when compared with their HIV-negative counterparts.…”
Section: Infectious/para-infectiousmentioning
confidence: 99%
“…The authors further demonstrated that the p75ntr supports Purkinje neuron survival in the presence of trophic factors but promotes autophagy and death of Purkinje neurons in the absence of trophic stimuli [ 173 ]. Emerging studies suggest that HIV +ve /HD patients exhibit an earlier onset of HD symptoms than HIV −ve /HD patients [ 174 , 175 , 176 ]. Studies also demonstrated that in these patients, dysregulation of neuronal autophagy was associated with HIV-1 dementia and encephalitis [ 167 , 168 ].…”
Section: Neurons Autophagy and Agingmentioning
confidence: 99%